2011
DOI: 10.1111/j.1399-0012.2011.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, presentation, and endovascular management of hemodynamically or clinically significant arterio‐portal fistulae in living and cadaveric donor liver transplant recipients

Abstract: Significant APF are a rare diagnosis (0.2% of transplants). Coil embolization is a safe and effective treatment option for APF in transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…Post-discharge, there was complete resolution of the ascites. Pediatric APFs are rare, usually associated with hepatic trauma or needle intervention (2). Mieles et al reported a 12-month-old with an APF following a segmental liver transplantation, successfully managed with transcatheter coil embolization (1).…”
Section: Dear Editormentioning
confidence: 99%
“…Post-discharge, there was complete resolution of the ascites. Pediatric APFs are rare, usually associated with hepatic trauma or needle intervention (2). Mieles et al reported a 12-month-old with an APF following a segmental liver transplantation, successfully managed with transcatheter coil embolization (1).…”
Section: Dear Editormentioning
confidence: 99%
“…1,8,9 This is despite the fact that liver transplant recipients undergo numerous percutaneous procedures (liver biopsies and percutaneous transhepatic cholangiograms) and are under constant imaging surveillance. [1][2][3] This may shed light as to the pathogenesis of hemodynamically significant APFs. [1][2][3]10 Etiology and Pathogenesis APFs are considered arterial injuries leading to a connection between the high-pressure hepatic artery and an adjacent lower-pressure portal vein branch.…”
mentioning
confidence: 98%
“…[1][2][3] This may shed light as to the pathogenesis of hemodynamically significant APFs. [1][2][3]10 Etiology and Pathogenesis APFs are considered arterial injuries leading to a connection between the high-pressure hepatic artery and an adjacent lower-pressure portal vein branch. [1][2][3]8,[11][12][13][14][15] APFs are believed to be a product of percutaneous transhepatic procedures such as percutaneous liver biopsies and percutaneous transhepatic cholangiograms (PTCs) with or without percutaneous biliary drain placement, hence the presumed etiology of iatrogenic vascular injury.…”
mentioning
confidence: 98%
“…Doppler ultrasonography is particularly useful because it has high sensitivity and specificity for hemodynamically significant hepatic artery to portal vein fistulas. [17][18][19] Treatment of this rare condition is mainly endovascular, with surgery reserved for complex cases. 17,20,21 Embolization is also challenging as the actual fistulous communication is very short and liver allografts are relatively hypoperfused and hence susceptible to ischemia.…”
Section: Hepatic Artery To Portal Vein Fistulasmentioning
confidence: 99%
“…Attention to proper technique and the proper embolic agent is important. 17,19 For hepatic artery to portal vein fistulas, the embolic agent should be selected according to the size of the vascular communication and flow. In larger fistulas with high flow, there is risk of distal migration and portal vein thrombosis.…”
Section: Hepatic Artery To Portal Vein Fistulasmentioning
confidence: 99%